Recessions and recoveries in Asia: What can the past teach us about the present recession? - Souvik Gupta; Jacques Miniane (Asian Development Bank Institute (ADBI), 2009)
With the global economy still in recession, two important questions arise for Asia: how soon will the recession end, and how vigorous will the region's recovery be? The purpose of this paper is to look at past recessions and recoveries in Asia in order to shed light on these issues. Several important stylized facts emerge from this study: (i) recessions accompanied by financial stress - notably, stress in domestic banking sectors - have been substantially longer and deeper than the norm, suggesting that the current recession could have been even costlier and more drawn out had Asia's banks not entered the downturn in such strong shape; (ii) recoveries in Asia have been weak because they were typically driven by a single engine: exports. In contrast, other emerging economies have tended to experience more vigorous recoveries because of a stronger contribution from domestic demand, notably investment; (iii) in Asia, deep recessions have resulted in substantial declines in potential output growth, meaning that their effects are not just cyclical but permanent. A clear lesson emerges from past experience: given the expected weak recovery in the eurozone and the United States, Asia should not count on exports to rebound strongly as it did in previous upturns. Rather, a fundamental rebalancing towards domestic demand is needed if Asia wants to preserve the high growth rates that have characterized its recent past. Finally, it remains to be seen whether potential output will fully recover from pre-crisis levels in the countries most affected by the crisis.
Keywords: E32; E65; G01; 330